2014
DOI: 10.1111/cas.12541
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of STRN4 suppresses the malignant characteristics of cancer cells

Abstract: The striatin family of proteins, comprising STRN, STRN3 and STRN4, are multidomain-containing proteins that associate with additional proteins to form a large protein complex. We previously reported that STRN4 directly associated with protein kinases, such as MINK1, TNIK and MAP4K4, which are associated with tumor suppression or tumor progression. However, it remains unclear whether STRN4 is associated with tumor progression. In this report, we examined the role that STRN4 plays in cancer malignancy. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 38 publications
1
52
0
1
Order By: Relevance
“…2B). Reduced cell proliferation can be induced by a delay in cell cycle progression or by the promotion of cellular apoptosis (21). To determine how TRIP13 depletion suppressed cell proliferation, a terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay and an EdU incorporation assay were performed.…”
Section: Depletion Of Trip13 Suppresses Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…2B). Reduced cell proliferation can be induced by a delay in cell cycle progression or by the promotion of cellular apoptosis (21). To determine how TRIP13 depletion suppressed cell proliferation, a terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay and an EdU incorporation assay were performed.…”
Section: Depletion Of Trip13 Suppresses Cell Proliferationmentioning
confidence: 99%
“…To determine how TRIP13 depletion suppressed cell proliferation, a terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay and an EdU incorporation assay were performed. The TUNEL assay detects fragmented DNA induced by apoptosis, while the EdU incorporation assay evaluates cell cycle progression (21). Cells that progress through the S phase incorporate the thymidine analog EdU; thus, proliferating cells can be detected based on the level of EdU incorporated (21).…”
Section: Depletion Of Trip13 Suppresses Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…DJ-1 has also been associated with cancer cell survival and metastasis. Recently, it has been shown that downregulation of striatin 4/zinedin, the third member of striatin family, reduces cancer cell survival [28]. We thus asked whether SG2NA being a scaffold for both DJ-1 and Akt, promotes cancer cell proliferation.…”
Section: Downregulation Of Sg2na Decreases Cancer Cells Growthmentioning
confidence: 98%
“…Out of the 15 genes, 9 of them have been reported to be associated with cancer. These include genes which are reported to be related with breast cancer: PMP22 (Winslow et al, 2013), AIM2 (Liu et al, 2015), colorectal cancer: CNGA3 (Shaikh et al, 2015), ovarian cancer HOXB8 (Stavnes et al, 2013), liver cancer HNF4A (Ning et al, 2010), pancreatic cancer PCDHB2 (Carter et al, 2010), and cancer progression STRN4 (Wong et al, 2014), CHCHD4 (Yang et al, 2012), and VHL (Kim and Kaelin, 2004), where the number in the parenthesis is the rank of p-value among the 15 genes.…”
Section: Application To Dna Methylation Data Of Ovarian Cancermentioning
confidence: 99%